Integration into university life among students residing in dorms - EL-MNEIZEL, A.F; AL-GHARAIBEH, F (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The aim of this study is to measure the level of integration of students residing in dorms at the University of Sharjah in the United Arab Emirates. The sample of the study comprised a total of (1215) male and female students. Student Integration into University Life questionnaire (SIULQ) were distributed to the sample of the study during the second semester of the academic year 2017-18. The results show that there are statistically significant differences in three subscales (participation in activities and events, social bonding and compatibility, and attachment) among students of different colleges in favour of students of humanities.